ChemInform Abstract: Ruthenium‐Catalyzed Silylation of 1, 3‐Butadienes with Vinylsilanes. Issue 39 (September 2015) - Szudkowska‐Fratczak, Justyna; Marciniec, Bogdan; Hreczycho, Grzegorz; Kubicki, Maciej; Pawluc, Piotr
Abstract leading to (E, E)‐dienylsilanes (III) as main products